A phylogenetic assessment of the meadow lizard Darevskia praticola (Eversmann, 1834) from Iran - Saberi-Pirooz, Reihaneh; Ahmadzadeh, Faraham; Ataei, Saeedeh; Taati, Mehrnaz; Qashqaei, Ali Turk; Carretero, Miguel A. (Zootaxa, 2018)
The meadow lizard Darevskia praticola (Eversmann, 1834) displays a wide distribution range from the Western Balkans and Caucasus to the Hyrcanian forest in Iran. Based on previous studies, four subspecies have been described (D. p. praticola, D. p. pontica, D. p. hyrcanica and D. p. loriensis), but molecular evidence suggests two main phylogenetic lineages, Balkan and Caucasus. In this study we incorporated geographic records and analysed new samples from Alborz Mountains (Gilan Province, Iran), exploring their phylogenetic affinities using two mitochondrial markers (Cyt b and ND4). For the first time, Iranian samples are included in a molecular phylogeny. Our results meet the previous suggestions regarding the presence of a nuclear mitochondrial DNA fragment (numt) in Cyt b, causing misleading phylogenetic inferences since it renders the species paraphyletic. In contrast, the ND4 genealogy groups the species into a monophyletic clade, as expected. Samples attributed to D. p. hyrcanica (Azerbaijan and Iran) and D. p. loriensis (Armenia) are settled in a single clade with minute genetic distance, suggesting synonymisation.